2008
DOI: 10.1017/s0033291708004169
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized controlled trial of cognitive behaviour therapy for common mental disorders in patients with advanced cancer

Abstract: It is possible to conduct a randomized trial of psychological interventions in palliative care but there is considerable attrition from physical morbidity and mortality. Nurses can learn to integrate basic CBT methods into their clinical practice. This training may be associated with better outcomes for symptoms of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 30 publications
8
80
0
10
Order By: Relevance
“…As shown in Table 1, the 14 studies of interventions to reduce psychological distress we reviewed included 12 studies of patients with mixed cancer sites [34][35][36][37][38][39][40][41][42][43][44][45], 1 study with patients with breast or cervical cancer [46], and 1 study with patients with breast cancer only [47]. Total sample size per study ranged from 55 to 472.…”
Section: Review Question #1: Effect Of Treatment Of Psychological Dismentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, the 14 studies of interventions to reduce psychological distress we reviewed included 12 studies of patients with mixed cancer sites [34][35][36][37][38][39][40][41][42][43][44][45], 1 study with patients with breast or cervical cancer [46], and 1 study with patients with breast cancer only [47]. Total sample size per study ranged from 55 to 472.…”
Section: Review Question #1: Effect Of Treatment Of Psychological Dismentioning
confidence: 99%
“…The other 10 studies included collaborative care interventions [35,37,40,44,46], cognitive behavior therapy [36,39,41], problem solving therapy [42], and aromatherapy massage [45]. Among the drug trials, there was 1 study [38] with at least 64 patients per group, and that study found a small effect size reduction on self-reported depressive symptoms with fluoxetine (Hedges's g = 0.23).…”
Section: Review Question #1: Effect Of Treatment Of Psychological Dismentioning
confidence: 99%
“…Muchos de los estudios iniciales sobre la eficacia de los tratamientos psicoló-gicos se han llevado a cabo con especialistas entrenados y con experiencia. Sin embargo, un creciente número de estudios sugiere que clínicos sin formación específica en Psiquiatría o en Psicología pueden aplicar dichas intervenciones con eficacia (Moorey et al, 2009;Narayan, Kanaya, & Gregg, 2003), ampliándose así la disponibilidad de recursos para afrontar de forma integrada fenómenos cruciales para la salud, desde el estilo de vida hasta las conductas de enfermedad.…”
Section: Integración De Las Intervenciones Psicológicas En Medicinaunclassified
“…Psychological interventions (e.g., Cognitive Behavioral Therapy, CBT) have been shown to reduce psychological distress in chronic disease populations [12][13][14]. Although psychological interventions are increasingly desirable among patients [15], there are several barriers to accessing face-to-face psychological care among people with chronic health conditions (e.g., cost/insurance coverage, access, stigma) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%